EVALUASI MANFAAT PENERAPAN CLINICAL PATHWAY SECTIO CAESAREA DI RUMAH SAKIT BETHESDA LEMPUYANGWANGI - Ferni (Journal of Health Service Management, 2024)
Background: Cesarean section (SC) is one of the most performed surgical procedures in the world, as well as in Bethesda Lempuyangwangi Hospital (RSBL). This action is included in the high volume and high-cost category, so a guide is needed to reduce variations in patient care. Clinical pathway (CP) is a tool to improve the process of preparation, management, and clinical outcomes of patients. RSBL has developed a CP for SC since 2019, but there has never been an evaluation of the benefits of its implementation. Objectives: To evaluate the benefits of SC CP implementation on laboratory test compliance, prophylactic antibiotic prescribing compliance, incidence of surgical wound infection, length of stay, and APGAR score. Methods: This was an observational analytic study with an ex-post facto research design. The subjects of this study were all patients undergoing elective SC surgery at RSBL who met the inclusion criteria in the period before and after the implementation of SC CP. The variables evaluated were compliance with laboratory tests, compliance with prophylactic antibiotic prescribing, incidence of surgical wound infection, length of stay, and APGAR score. Results: Compliance of laboratory tests increased from 6.7% to 100%, compliance of prophylactic antibiotic prescribing increased from 3.4% to 84.3%, the incidence of surgical wound infection decreased from 1.10% to 0.0%, and variation in the length of stay decreased from 2-4 days to 3 days (100%). The mean first-minute APGAR score did not change (7), while the 5th and 10th-minute scores decreased from 9 to 8, and 10 to 9, respectively. Conclusions: The implementation of CP SC was beneficial in improving laboratory testing compliance and prophylactic antibiotic prescribing compliance, reducing the incidence of surgical wound infection, and reducing variation in the length of stay, but could not improve the APGAR score. Keywords: Clinical pathway, sectio caesarea, laboratory testing, prophylactic antibiotic, length of stay